Implementation of Sharia Marketing in the Real Estate Industry During the Covid-19 Pandemic Using a SWOT Analysis - Afrida Zahira; Irvan Iswandi; Ali Aminullah (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
The growth in property sales volume starting at the end of 2020 has decreased due to the emergence of the pandemic. In order to support the recovery of the property market, the government has taken various ways to make it happen, which can be used by property business players to maximize sales and determine sharia marketing strategy policies for property products thus they can survive and continue to grow during the Covid-19 pandemic. Based on this background, the writer was interested in researching the implementation of sharia marketing strategies and conducting a SWOT analysis at PT Reswara Makmur Propertindo. The research method used in this study was a combination of library research and field research with a qualitative approach. The results of the study showed that the company has fulfilled the characteristics of sharia marketing and has implemented a sharia marketing mix in marketing products/house units. From the results of the evaluation of the Internal External matrix, it obtained a value of (2.30 ; 2.70), which means that the company occupies a stable or growing position. The strategy that can be taken is a horizontal integration strategy or not making any changes to the strategy. A horizontal integration strategy can be carried out by increasing the size of the company, and increasing sales, profits, and potential market of the company. Meanwhile, the results of the SWOT quadrant analysis show that the company is at coordinates (0.70 ; 1.00), namely quadrant 1. The priority strategy that can be applied by the company is the S-O strategy, namely increasing market share by targeting the millennial generation as the target market, creating products with innovations that can accommodate the needs and desires of the millennial generation, maximizing the function of the marketing office for personal selling, providing understanding to consumers through social media content regarding government stimulus in the property sector..